2006
DOI: 10.1016/j.neuropharm.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

κ-Opioid receptor modulation of accumbal dopamine concentration during operant ethanol self-administration

Abstract: Our study examined ethanol self-administration and accumbal dopamine concentration during κ-opioid receptor (KOPr) blockade. Long-Evans rats were trained to respond for 20 min of access to 10% ethanol (with sucrose) over 7 days. Rats were injected s.c. with the long-acting KOPr antagonist, nor-binaltorphimine (NOR-BNI; 0 or 20 mg/kg) 15-20 h prior to testing. Microdialysis revealed a transient elevation in dopamine concentration within 5 min of ethanol access in controls. NOR-BNItreated rats did not exhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…These results are consistent with the hypothesized upregulation of dynorphin systems observed following chronic ethanol as suggested by decreased mRNA for k-opioid receptors in the NAc and VTA (Rosin et al, 1999), as well as increased expression of dynorphin B in the NAc (Lindholm et al, 2000). The present data are also consistent with previous research which found that nor-BNI did not affect nondependent ethanol self-administration (Doyon et al, 2006) or consumption of ethanol within the context of the alcohol deprivation effect (Holter et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the hypothesized upregulation of dynorphin systems observed following chronic ethanol as suggested by decreased mRNA for k-opioid receptors in the NAc and VTA (Rosin et al, 1999), as well as increased expression of dynorphin B in the NAc (Lindholm et al, 2000). The present data are also consistent with previous research which found that nor-BNI did not affect nondependent ethanol self-administration (Doyon et al, 2006) or consumption of ethanol within the context of the alcohol deprivation effect (Holter et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…DYN's relationship with alcohol and other drugs stems from its ability to modulate other neurotransmitters such as dopamine (DA), GABA, glutamate, and serotonin. Activation of the DYN/KOR system has been found to modify DA in the Acb following cocaine (Thompson et al, 2000) and ethanol use (Doyon et al, 2006). The DYN/KOR system also modulates dopaminergic neurons projecting to the prefrontal cortex (Margolis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As the effect of chronic alcohol consumption upon mGluR1/Homer2a/b/NR2b expression is enduring (Figure 1), this neuroadaptation may underlie the development of excessive alcohol intake, a defining feature of alcoholism, as well as contribute to the chronic, relapsing nature of this disease. Doyon et al, 2003Doyon et al, , 2004Doyon et al, , 2006Gonzales and Weiss, 1998;Melendez et al, 2002;Middaugh et al, 2003;Szumlinski et al, 2007;Weiss et al, 1993) and sensitizes the capacity of alcohol to elevate NAC glutamate . While neither Homer1 nor Homer2 proteins appear to be necessary for the regulation of NAC basal dopamine content, deletion of Homer1 or Homer2 produces a number of glutamatergic abnormalities within this region that have been implicated in regulating sensitivity to several drugs of abuse (Szumlinski et al, 2006c).…”
Section: Accumbens Homer2b Upregulation Promotes Alcohol Rewardmentioning
confidence: 99%